Old Age - Vincent, John (Key Ideas, 2003)
Recent decades have seen a fundamental change in the age structure of many western societies. In these societies it is now common for a fifth to a quarter of the population to be retired, for fewer babies to be born than is required to sustain the size of the population and for life expectancy to exceed eighty years old. This book provides an overview of the key issues arising from this demographic change.